Answer:
B. 13
Explanation:
[tex]\sf\:Given\:expression: log(\dfrac{x^2 y^3}{z} )[/tex]
Logarithm rules:
[tex]\sf (i) \ \sf log(ab) = log(a) + log(b)\\ \\ (ii) \ log(a/b) = log(a) - log(b)\\\\ (iii) \ log(a^n) = n log(a)[/tex]
Breakdown of the expression:
[tex]\rightarrow \sf log\left(\dfrac{x^2y^3}{z}\right)[/tex]
[tex]\rightarrow \sf log\left(x^2\right) + log\left(y^3\right) - log(z)[/tex]
[tex]\rightarrow \sf 2\log\left(x\right)+3\log \left(y\right)-\log \left(z\right)[/tex]
insert given values
[tex]\rightarrow \sf 2(3)+3(2)-(-1)[/tex]
[tex]\rightarrow \sf 13[/tex]